2021
DOI: 10.1186/s41938-021-00399-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of entomopathogenic nematodes (Rhabditida: Heterorhabditidae and Steinernematidae) on the codling moth (Cydia pomonella L.) (Lepidoptera: Tortricidae) under controlled conditions

Abstract: Background The codling moth (CM), Cydia pomonella (L). (Lepidoptera: Tortricidae), is an important pest of apple in Turkey and other apple producing countries in the world. Several control methods are available for reducing the pest populations. Entomopathogenic nematode (EPNs), for example, can be used as a potential alternative to chemical insecticides to control codling moth larvae in the soil as eco-friendly management their hosts that can actively find them in cryptic locations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
2
4
1
Order By: Relevance
“…However, S. carpocapsae performed better than H. bacteriophora. In another study conducted by Ya gci et al [22], S. carpocapsae and S. feltiae exhibited superior virulence to H. bacteriophora against the first larvae of C. pomonella, which is contradictory to the findings of this study. In a previous study evaluating the field performance of different EPN species against C. pomonella larvae, S. feltiae and S. carpocasae caused similar mortalities at concentrations of 50 IJs/mL [12].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, S. carpocapsae performed better than H. bacteriophora. In another study conducted by Ya gci et al [22], S. carpocapsae and S. feltiae exhibited superior virulence to H. bacteriophora against the first larvae of C. pomonella, which is contradictory to the findings of this study. In a previous study evaluating the field performance of different EPN species against C. pomonella larvae, S. feltiae and S. carpocasae caused similar mortalities at concentrations of 50 IJs/mL [12].…”
Section: Discussioncontrasting
confidence: 99%
“…Although EPNs are soil-originated organisms, their ability to find and infect insect pests in cryptic habitats such as crevices in wood and litter at the base of trees where the fifth instar larvae of C. pomonella choose to pupate makes them a perfect candidate for the biological management of orchards [18]. Earlier laboratory and field studies showed that first and fifth instar C. pomonella larvae were susceptible to EPNs [19][20][21][22]. However, to our knowledge, there is no study assessing the effectiveness of EPNs recovered from apple orchards on the larvae of C. pomonella.…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that the EPNs could be effective biological control agents against EGVM larvae and pupae in vineyards. In agreement with previous studies against other tortricid species, including L. vanillana, EPN virulence differed among nematode species [35,38,39,41,42]. As observed for C. pomonella [38], our S. carpocapsae population resulted in being the most virulent against the various larval and pupal stages.…”
Section: Entomopathogenic Nematodes As Biological Control Agents Against Larvae and Pupae Of The European Grapevine Mothsupporting
confidence: 91%
“…In agreement with previous studies against other tortricid species, including L. vanillana, EPN virulence differed among nematode species [35,38,39,41,42]. As observed for C. pomonella [38], our S. carpocapsae population resulted in being the most virulent against the various larval and pupal stages. However, the virulence varied depending on the larval instar, with L1 being the least susceptible, which was probably due to size reasons and may have been too small for EPN.…”
Section: Entomopathogenic Nematodes As Biological Control Agents Against Larvae and Pupae Of The European Grapevine Mothsupporting
confidence: 91%
See 1 more Smart Citation